Dichotomy between macrophage activation and degree of protection against Listeria monocytogenes and Toxoplasma gondii in mice stimulated with Corynebacterium parvum. - Swartzberg, J E (1975)
In vivo and in vitro experiments were conducted to determine the effect of Corynebacterium parvum treatment of mice on resistance of Listeria monocytogenes and Toxoplasma gondii. Intravenous immunization with C. parvum conferred transient protection against intravenous challenge with Listeria or an avirulent strain of Toxoplasma but did not protect against a virulent strain of Toxoplasma. Compared with the level of protection conferred by C. parvum, a higher degree of resistance was noted when mice infected with Listeria or Toxoplasma were challenged with the homologous infecting organism. Peritoneal macrophages from mice immunized intravenously with C. parvum were activated to kill Toxoplasma in vitro. Whereas resistance to challenge in vivo was transient, this population of activated macrophages persisted. Peritoneal macrophages from C. parvum mice also markedly inhibited [3H]thymidine uptake by L cells.